KAJIAN PENULISAN TUGAS AKHIR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JAWA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI YOGYAKARTA - - Suharti; Endang Nurhayati; Venny Indria Ekowati; Hartanto Utomo (Fakultas Bahasa Seni dan Budaya, 2016)
This study is proposed for eight months. The purposes of the study are: (1) identifying the fields of science and sub-fields of research science in the thesis or